Characterization of redox-active cysteine residues of persulfide-responsive transcriptional repressor SqrR. Issue 4 (4th July 2017) - Shimizu, Takayuki; Masuda, Shinji
ABSTRACT: We recently identified the novel persulfide sensor SqrR that functions as a master regulator of sulfide-dependent gene expression in the purple photosynthetic bacterium Rhodobacter capsulatus . SqrR binds to the promoter regions of target genes to repress their expression in the absence of sulfide, and the repressor activity is negated by sulfide treatment. SqrR has 3 cysteine residues, 2 of which are conserved in SqrR homologs from other bacteria: Cys41 and Cys107. SqrR forms an intramolecular tetrasulfide bond between Cys41 and Cys107 when exposed to persulfide, which results in loss of the DNA-binding activity in vitro . Here, we address the mechanism through which these cysteine residues are modified by persulfides. We show that the predicted p K a value of Cys107, as revealed by a putative SqrR structural model, is lower than that of Cys41. Furthermore, C41S SqrR in which Cys41 was changed to serine forms an intermolecular disulfide-bond between Cys107 of 2 SqrRs, suggesting high nucleophilic reactivity of Cy107. These data suggest that Cys107 and Cys41 function as attacking Cys and resolving Cys, respectively; this occurs during tetrasulfide-bond formation of WT SqrR, when it is exposed to persulfide.